Unlocking potential: The role of differentiated instruction in shaping English learning outcomes among EFL students in Takalar, South Sulawesi, Indonesia - M. Jufrianto; Muhammad Basri; Iskandar (Universitas Sulawesi Barat, 2025)
This study examined the effectiveness of differentiated instruction (DI) in improving English reading comprehension and attitudes among Grade XII students at SMA Negeri 3 Takalar, South Sulawesi, Indonesia. Notwithstanding the Indonesian government’s focus on English language instruction, numerous learners encountered considerable obstacles in attaining competency. The research adopted a mixed method with a quasi-experimental design comprising 216 students, categorized into DI and Non-DI groups, to evaluate the effects of differentiated instruction compared to conventional teaching methods. Analyses of preliminary test and post-test results indicated that the DI group, which utilized a differentiated instruction strategy, exhibited substantial enhancements in reading comprehension, attaining superior mean scores relative to the non-DI group. Qualitative evidence obtained from teacher observations and student surveys revealed favorable impressions of differentiated instruction, emphasizing heightened involvement and motivation among students. Nonetheless, problems, including time restrictions and budget limitations, were observed. The Findings highlight the need for a differentiated instruction strategy to address varied learning requirements, enhancing English language training in Indonesian educational settings. The findings emphasize the necessity of employing customized instruction methodologies to meet varied learning demands, hence improving English language education in Indonesian settings. Research implications suggest that teachers require specialized professional development in differentiated instruction to adeptly customize instructional techniques and resources, thereby enhancing student outcomes and promoting a more inclusive learning environment. The study underscores the necessity for educational policymakers and curriculum developers to integrate differentiated instruction into national teaching frameworks, especially in English language education. Educational institutions should prioritize the provision of training programs and practical workshops to equip teachers with the skills needed to implement DI effectively. Additionally, resource allocation should be improved to support the adaptation of instructional materials to suit students’ varying readiness levels, interests, and learning profiles. Future research is encouraged to explore the long-term impact of DI across different subjects and educational levels, as well as to investigate scalable models for its implementation within resource-constrained school systems in Indonesia.